ANALISIS PENGARUH MEREK, POTONGAN HARGA DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PT RAMAYANA LESTARI SENTOSA Tbk di KOTA BATAM - Nora Pitri Nainggolan (LPPM Universitas Putera Batam, 2018)
Competition in business today is increasingly stringent, companies are demanded to offer quality products and who are able to have more value so different from the product competitors. This study aims to determine the influence of brands, discounts and advertising to consumer purchasing decision.. The research design used in this research is quantitative research. The sample used is 200 respondents with Accidental Sampling method. Data analysis method consisted of validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient determination test, T test and F test. The results showed all the data valid and reliable. The result of T test explain that brands, discount partially have a significant effect to consumer purchasing decision, but advertising partially has no a significant effect to consumer purchasing decision. From the F test the result explain than brands, discount, and advertising simultaneously have a significant effect to consumer purchasing decision.